Evaluation of lactic acid bacteria isolated from alfalfa for silage fermentation. (25th March 2018) - Li, Dongxia; Wang, Yanping; Zhang, Yingchao; Lin, Yanli; Yang, Fuyu
Abstract: The present study isolated 84 strains of lactic acid bacteria (LAB) 38 alfalfa cultivars in China and evaluated their effectiveness at improving alfalfa silage quality. The strains, belonging to seven genera, 15 species and subspecies were identified based on phenotypic and chemotaxonomic characteristics, 16S rDNA sequencing and rec A gene polymerase chain reaction (PCR) amplification. The LAB, predominantly Leuconostoc (46.4%), consisted of Leuconostoc mesenteroides subsp. mesenteroides (22.6%), Leuconostoc lactis (2.4%), Leuconostoc fallax (7.1%), Leuconostoc citreum (1.2%), Leuconostoc pseudomesenteroides (13.1%), Enterococcus hirae (8.3%), Enterococcus casseliflavus (8.3%), Enterococcus faecium (6.0%), Streptococcus parauberis (2.4%), Weissella cibaria (2.4%), Weissella confusa (11.9%), Pediococcus pentosaceus (6.0%), Lactococcus lactis subsp. lactis (2.4%), Lactococcu garvieae (2.4%) and Lactobacillus plantarum subsp. plantarum (3.5%). Among the isolates, Lactobacillus plantarum subsp. plantarum ZZU A18 showed notable ability to decrease the pH in alfalfa broth and exhibited excellent effect to improve alfalfa silage quality. Compared to silage treated with or without a commercial silage additive, inoculation with L. plantarum subsp. plantarum ZZU A18 significantly increased the production of lactic acid and acetic acid, preserved the dry matter and crude protein content, decreased the pH and concentrations of propionic acid, butyric acid, ammonia‐nitrogen and inhibited undesirable microorganisms. In brief, strain ZZU A18 was considered as an effective inoculant for alfalfa silage.